TASAWUF DALAM PANDANGAN NURCHOLISH MADJID - Ilham Masykuri Hamdie (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2015)
Although Sufism is not a central theme of Nurcholish Madjid works, thisarticle will discuss aspects of Sufism in Nurcholish Madjids point of viewbecause his ideas of renewal which is loaded with depth of knowledge,modernity and humanity, show an appreciative attitude towards Sufism. Thisdiscussion found that Nurcholish Madjid notice the essence of diversity inSufism such as taqarrub, the meaning of worship, akhlak al-karimah (gooddeed), and actively involved in social life. Those points are very relevant toreligious life now and in the future.